CONTEXTUALIZATION OF ISLAMIC EDUCATION IN THE THEME OF CIVIL SOCIETY 5.0 (HUMAN RIGHTS, GENDER AND PLURALISM) - Rega Armella; Zamroni Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The era of Civil Society 5.0 requires a new paradigm in education, including Islamic education, to respond to humanitarian challenges amid rapid digitalization. Islamic education is not only a means of transmitting knowledge and religious values but also an instrument for shaping a civil society that upholds Human Rights (HR), gender equality, and pluralism. In this context, Islamic education must integrate universal values into curricula, learning processes, and social practices, thereby fostering a Muslim generation that is inclusive, critical, and adaptive to contemporary changes. Contextualizing Islamic education within the framework of Civil Society 5.0 means harmonizing Islamic teachings with the demands of a technology-based modern society without losing its spiritual and moral essence. Thus, Islamic education has the potential to serve as a driving force in building a civilized society that balances religious, humanistic, and digital dimensions.